PELAKSANAAN SISTEM LAYANAN RESERVASI KAMAR PADA FRONT OFFICE DEPARTEMENT GRAND ROCKY HOTEL KOTA BUKITTINGGI - Indah Intan Permata Sari; Siti Sofro " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The Reservation Section which is affiliated with the Telephone Operator at the Front Office Department of Grand Rocky Hotel Bukittinggi has the main task of handling the guest room reservation process. The Reservation Section certainly has procedures that are used as guidelines in serving guest room reservations. Therefore, the authors are interested in examining the implementation of a room reservation service system at the Front Office Department of the Grand Rocky Hotel Bukittinggi. This study aims to analyze the room reservation service system at Grand Rocky Hotel Bukittinggi. The history of the establishment of the Grand Rocky Hotel began with its sister Hotel Rocky in Padang – West Sumatra, namely the Rocky Plaza Hotel. Grand Rocky Hotel was established in 2012, which is located at Jl. Yos Sudarso No.29, Kayu Kubu, Kec. Guguk Panjang, Bukittinggi City, West Sumatra. This study uses a qualitative method to analyze a set of cases, which became the key informants in this study as many as three people. Namely 1 Front Office Manager, 1 Front Office Supervisor and 1 Front Desk Agent. Sources obtained through interviews, observation, and documentation. Based on the results of this study, the conclusion of this study is that the reservation service system at the Front Office Department of Grand Rocky Hotel Bukittinggi has followed the procedure, but still needs to be improved so that the reservation service system in the future is even better. Keywords: Service, Reservation, Front Office, Hotel